PENERAPAN TEKNOLOGI TEPAT GUNA ECO ENZYME DAN SABUN PADAT DI DESA CIPTAHARJA - Lusi Marlina; Myra Wardati; Chengrishtama Chengrishtama; Reni Listiana (PUAN INDONESIA, 2026)
ThisThe Community Service Program sought to boost community awareness and abilities in managing household organic waste by introducing straightforward technologies, specifically eco-enzyme production and eco-friendly solid soap making. It employed extension lectures and practical training sessions, with village residents as primary participants. Key topics included foundational waste management principles, the eco-enzyme fermentation method, and safe, readily available techniques for crafting solid soap. Outcomes revealed enhanced participant comprehension and hands-on expertise in converting organic waste into valuable products. Strong attendance and keen interest underscored the success of participatory methods in building environmental consciousness. Ultimately, the initiative is poised to advance sustainability goals and empower communities for independent, eco-friendly waste handling.